When to ease off the brakes (and hopefully prevent recessions) - Harold M. Hastings; Tai Young-Taft; Thomas Wang (Levy Economics Institute of Bard College, 2019)
Increases in the federal funds rate aimed at stabilizing the economy have inevitably been followed by recessions. Recently, peaks in the federal funds rate have occurred 6-16 months before the start of recessions; reductions in interest rates apparently occurred too late to prevent those recessions. Potential leading indicators include measures of labor productivity, labor utilization, and demand, all of which influence stock market conditions, the return to capital, and changes in the federal funds rate, among many others. We investigate the dynamics of the spread between the 10-year Treasury rate and the federal funds rate in order to better understand "when to ease off the (federal funds) brakes".
Keywords: C40; C60; E17; E42; E52; 330; Federal Funds Rate; Yield Curve; Monetary Policy; Nonlinear Dynamics; Takens' Embedding